The validity and reliability of modified cough transport outcome using slower airflow for assessing mucus viscoelasticity - Aung Aung Nwe; Kosura, Nimit; Phimphasak, Chatchai; Barnludech, Pornthip; Aung, Sithu; Chumpangern, Worawat; Hongrattana, Guntaragorn; Kluayhomthong, Sujittra; Domthong, Pornanan; Reechaipichitkul, Wipa; Jaimanee, Chatchaya; Chatchawan, Uraiwon; et al. (Journal of Associated Medical Sciences, 2024)
Background: The cough transportability technique reflects changes in mucus rheology. However, the necessity of high airflow rates, such as 8 L/s, to carry out this technique limits its utility, as specialized setups or equipment are required. Objective: This study aims to identify practical alternatives to higher airflow rates and utilize easily accessible equipment, such as mechanical air pumps (2 L/s). Materials and methods: Mucus simulant gel (MSG) of 4 viscoelasticity and sputum from patients with bronchiectasis were collected and prepared. All samples underwent standard airflow cough transport (sCT) and modified cough transport (mCT). Additionally, three rounds of each MSG and two rounds of sputum underwent mCT. Results: A Pearson correlation analysis between mCT and sCT revealed very high (r=0.986, p=0.014) and high (r=0.771, p<0.001) in the MSG and the sputum of bronchiectasis patients, respectively. The test-retest reliability of mCT revealed ICCs of 0.997 and 0.926 in the MSG and sputum of patients with bronchiectasis, respectively.> Conclusion: mCT could be an alternative to sCT, offering a more accessible option for conducting cough transportability